Using Survey Data to Identify Migration Patterns - Stephen Drinkwater (WISERD, 2011)
This briefing focuses on the difficulty in obtaining the information needed to identify patternsof (temporary) migration, which appear to have become more diverse in recent years,facilitated by developments in transportation and increased globalisation. It is mainlyconcerned with examining how survey data may be used to shed further light on the issue. Itappears that the migration questions that have recently been added to the UK Labour ForceSurvey (LFS) are not that helpful in this respect. However, utilising the panel element of theLFS is likely to provide a far more fruitful avenue for future research. Some interestingpatterns can be identified in the basic application of this approach but more refined analysisis required in order to overcome some of the complicating factors that arise.